2012
DOI: 10.1055/s-0032-1315131
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer 2012 - New Aspects

Abstract: Treatment options as well as the characteristics for therapeutic decisions in patients with primary and advanced breast cancer are increasing in number and variety. New targeted therapies in combination with established chemotherapy schemes are broadening the spectrum, however potentially promising combinations do not always achieve a better result. New data from the field of pharmacogenomics point to prognostic and predictive factors that take not only the properties of the tumour but also inherited genetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 73 publications
0
17
0
2
Order By: Relevance
“…This topic has been investigated in recent studies with inconsistent results. Contrary to the prognostic markers, predictive markers shall support in decision making of certain therapies as they appreciate the potential to respond to a therapy [5254]. Various studies have explored the predictive value of Ki-67-labeling index of which some of them reported an association between high-pretreatment Ki-67-labeling index and better responses to chemotherapy in the neoadjuvant setting [11, 5558] whereas other studies found no such association [47, 57, 5961].…”
Section: Discussionmentioning
confidence: 99%
“…This topic has been investigated in recent studies with inconsistent results. Contrary to the prognostic markers, predictive markers shall support in decision making of certain therapies as they appreciate the potential to respond to a therapy [5254]. Various studies have explored the predictive value of Ki-67-labeling index of which some of them reported an association between high-pretreatment Ki-67-labeling index and better responses to chemotherapy in the neoadjuvant setting [11, 5558] whereas other studies found no such association [47, 57, 5961].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment and prevention measures are increasingly taking into account the molecular classification that has been established during the last 10 years (Sorlie et al, 2001;Fasching et al, 2012;Kolberg et al, 2012;Schmidt et al, 2012). With regard to tumor characteristics, links have already been reported between certain molecular markers and BC risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale randomized controlled trials (RCTs) investigated the use of AIs as either a substitute or add-on to tamoxifen and showed a superiority of the AIs over tamoxifen in postmenopausal patients (Baum et al 2002 ; Thürlimann et al 2009 ; Coombes et al 2004 ; Goss et al 2003 ; Dowsett et al 2010 ). Different strategies including AIs are possible, e.g., upfront monotherapy or switch to an AI after 2–3 years of tamoxifen or switch to tamoxifen after 2–3 years of AIs, and extended adjuvant treatment with an AI after 5 years of tamoxifen (Lux et al 2013 ; Kolberg et al 2012 ). Currently, the prolongation of ET beyond 5 years is discussed.…”
Section: Introductionmentioning
confidence: 99%